The Influence of Participative Leadership and Ocbe on The Environmental Performance of PPSU Workers in Jakarta - Hidayati, Diah Irma; Purwandari, Dian Alfia; Vivanti, Diana (Sahabat Publikasi, 2025)
This study aims to analyze the influence of Participatory Leadership and Organizational Citizenship Behavior for the Environment (OCBE) on the environmental performance of Public Infrastructure and Facilities Handling (PPSU) officers in DKI Jakarta. A quantitative approach was used by distributing questionnaires to PPSU officers in 15 villages spread across DKI Jakarta. Data were analyzed using multiple linear regression. The results showed that participatory leadership and OCBE had a positive and significant effect on environmental performance, with a contribution of 67.9% to the model despite the indication of high multicollinearity between independent variables. These findings confirm the importance of collaborative leadership and voluntary pro-environmental behavior in supporting the performance of urban environments, especially in the public service sector.